Pengaruh Online Customer Review, Keamanan Bertransaksi, Dan Harga Terhadap Keputusan Pembelian Produk Kecantikan Skintific Pada E-Commerce Shopee (Studi Kasus Pada Mahasiswa FEB Angkatan 2020-2022 Universitas Islam Malang) - Syaidatul Khasanah; Nurhidayah Nurhidayah; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyse the influence of online customer reviews, transaction security, and prices on purchasing decisions for Skintific beauty products on Shopee e-commerce conducted on FEB students Batch 2020-2022 Islamic University of Malang. The type of research used is quantitative. The research sample was taken using proportioned stratified random sampling technique or proportional stratified random sampling using the Slovin formula, a total sample of 100 respondents. The data analysis method used in this study is multiple linear regression analysis. Using (F test) for simultaneous hypothesis testing and (t test) for partial testing. The results of this study indicaite thait simultaineously online customer reviews, trainsaiction security, aind prices haive ai significaint effect on purchaising decisions for Skintific beaiuty products on Shopee e-commerce. Meainwhile, pairtiailly online customer reviews haive no significaint effect on purchaising decisions, trainsaiction security pairtiailly hais ai significaint effect on purchaising decisions, aind prices haive ai significaint effect on purchaising decisions for Skintific beaiuty products on Shopee e-commerce. Keywords: Online Customer Reviews, Transaction Security, Prices, and Purchasing Decisions